Determination of Sediment Rating Curve In Dry Season In Bedagai Watersheds. (May 2020) - Susanto, E; Dawolo, S A; Rizaldi, T
Abstract: This research was conducted to overcome the problem of lack of sediment data in a watershed in North Sumatra due to the lack of sediment measurements recording which is caused by the amount of cost required, relatively long time, and the risk of obtaining such data. The purpose of this study was to obtain the equation of sediment curved line. Sediment curved line is an equation that connects the river discharge with the sediment discharge. The river discharge data could be used to obtain the sediment discharge. This research used descriptive methods in the form of primary data (debit data and sediment concentration) and secondary data (climate data). Results obtained sedimentary curved lines Qs = 18.995Qw1.9923 and R2 = 0.7451. The obtained sediment discharge has exceeded the limits set by the Ministry of Forestry regarding to the criteria for watershed determination.